Techniques of the World's best Part 5: Quick attack with Bas - Kortmann, O. (The Coach, 1999)
Can you tell us, what in your opinion are the most important characteristics in the quick attack? For me you can use the quick attack in two ways. As a go-to attack. That means that you set up a play to use the first tempo. When do you have the best chance to score a first tempo ball. That depends on opposite blocking and most reliable sets. Important here for the spiker is that he is quick and tries to find the holes. The spiker is asking the ball. He has to jump away from the block into the hole. The second ball is to set up outside-play. You must be in the middle of the net and be very quick. Important is that the reception is high so that the other middle blocker has to follow the ball and doesn't oversee all spikers. He will tend to jump if the first tempo spiker is on time. So be always on time. That's the most important.